Resource Discovery Third International Workshop, RED 2010, Paris, France, November 5, 2010, Revised Seleted Papers - Lacroix, Zoe; Vidal, Maria Esther (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2012)
This book constitutes the thoroughly refereed post-conference proceedings of the Third International Workshop on Resource Discovery, RED 2010, held in Paris, France, in November 2010. The 13 revised full papers - from 24 initial submissions - were carefully selected during a second round of reviewing and improvement from the lectures given at the workshop and are presented in extended version in the book. They deal with the following topics: resource discovery for composition; bioinformatics resource discovery; textual resource discovery; and Web service discovery.